2015
DOI: 10.1038/nnano.2015.221
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale cation motion in TaOx, HfOx and TiOx memristive systems

Abstract: A detailed understanding of the resistive switching mechanisms that operate in redox-based resistive random-access memories (ReRAM) is key to controlling these memristive devices and formulating appropriate design rules. Based on distinct fundamental switching mechanisms, two types of ReRAM have emerged: electrochemical metallization memories, in which the mobile species is thought to be metal cations, and valence change memories, in which the mobile species is thought to be oxygen anions (or positively charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
438
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 548 publications
(470 citation statements)
references
References 36 publications
25
438
1
1
Order By: Relevance
“…At the Pt/MeO x interface OH − can be incorporated (within nanopores) in accordance to Equation (5) or OH O • can be formed (according to Equation (1)). In the latter case this charge will also require compensation and will lead to reduction of the solid electrolyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the Pt/MeO x interface OH − can be incorporated (within nanopores) in accordance to Equation (5) or OH O • can be formed (according to Equation (1)). In the latter case this charge will also require compensation and will lead to reduction of the solid electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…However, new studies have demonstrated that the cations in such oxides are often mobile and can participate in the switching process as well. [5,6] Applying a voltage of opposite polarity, the formed filament is partially reoxidized within a thin region facing the high work function metal electrode, defining the OFF state. By modulation of the Schottky barrier at this interface reversible switching between the LRS and HRS is possible.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] There has been particular interest in understanding the role of migration of oxygen atoms in determining the operation of memristors. 6-11 Similar recent advances in understanding the localized nanoscale physico-chemical changes underlying resistance switching 4,12-15 have opened up fresh interests into studying the effect of atomic movements on extended device operation and the nanoscale material behavior during eventual failure and possible techniques to mitigate such failure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ambient effects on resistive switching suggest that the defects responsible for switching are hydrogen-passivated or are in some way protected from direct reaction with ambient oxygen and water until a switching events occurs [56,63]. The detailed interactions between ambient gases and proton (or cation) mobility is an important topic that may provide a deeper understanding of resistive switching mechanisms [64][65][66][67][68], specifically those in oxide-based valence change memory (VCM)-type ReRAMs [69][70][71]. The models used here to describe the possible SiO x -based RS mechanisms differ from most conventional models by considering that the defects responsible for RS may remain localized within the switching region so that resistive switching occurs when a collection of defects are driven between conductive and nonconductive forms [56].…”
Section: Resultsmentioning
confidence: 99%